Efficient management of wild oat (Avena fatua) and canary grass (Phalaris minor) in chickpea (Cicer arietinum) for higher productivity and profitability under irrigated condition - SINGH, R K; TRIPATHI, UTTAM KUMAR; SINGH, S R K; RAWAT, ANAY (The Indian Journal of Agricultural Sciences, 2020)
A field study was conducted during 2015-16 to 2017-18 on instructional farm of KVK, Panna under JNKVV, Jabalpur to evaluate the efficacy of clodinofop-propargyl, pendimethalin, and mechanical weed management of dominated weed flora wild oats (Avena fatua L.) and canary grass (Phalaris minor) in chickpea (Cicer arietinum L.). Clodinofop-propargyl was responsible for the reduction in wild oat & canary grass population consistently which resulted in the improvement of chickpea yield as compared to control plot. Post-emergence application of weedicide clodinofop-propargyl @ 60 g a.i/ha at 25-30 DAS effectively weed killing efficiency of wild oat and canary grass (86.9 and 81.25%) respectively, weed control efficiency 85%, weed index 39.1%, weed control index 92.8% and weedicide control efficiency 5.42% and their dry matter accumulation reduce 92.7% and increase the grain yield of chickpea 49.3% as compared to control plot. Under this trial cost benefit ratio was found 2.9 under recommended practices followed by mechanical weed management 2.5 as compared to control plot 1.8.